Inflammatory myopathies after allogeneic stem cell transplantation. Issue 6 (20th November 2018) - New‐Tolley, Julia; Smith, Caroline; Koszyca, Barbara; Otto, Sophia; Maundrell, Adam; Bardy, Peter; Hiwase, Devendra; Yong, Agnes S. M.; Lewis, Ian; Limaye, Vidya
ABSTRACT: Introduction, : Graft‐versus‐host disease (GVHD) is a recognized complication of allogeneic stem cell transplantation (allo‐SCT) and may affect muscle. We investigated the incidence and subtypes of inflammatory myopathy (IM) in South Australian recipients of allo‐SCT. Methods : Recipients of allo‐SCT from 2004 to 2014 at the Royal Adelaide Hospital were identified. Records were reviewed to identify patients with weakness, creatine kinase (CK) elevation, and muscle biopsy confirming IM. Results : Weakness was present in 32 of 224 patients who received allo‐SCT patients reviewed, and CK was raised in 7 of 20 patients with weakness. Six patients developed biopsy‐confirmed IM; 3 patients had chronic GVHD‐related myopathy, 2 had necrotizing myopathy, and 1 had dermatomyositis (DM) associated with anti–melanoma differentiation associated protein 5 (MDA5) antibodies. The incidence of IM was calculated to be 2 cases per thousand annually. Discussion : Among recipients of allo‐SCT, weakness is common, and the incidence of IM is increased. Histopathological diagnoses are varied, and we report findings of necrotizing myopathy and anti‐MDA5‐associated DM. Muscle Nerve 58 :790–795, 2018